EFL Teacher Agency in Merdeka Curriculum - Rachmawati Nur, Maulidia; Restu Luthfiani Maulida (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
Curriculum is undoubtedly a crucial part of education. In Indonesia, education curriculum has already undergone several changes. Among others, the newly introduced and implemented one is called â€œKurikulum Merdekaâ€. This study aimed to investigate how English teachers enact agency in English teaching process under curriculum change (Kurikulum Merdeka) and what are the challenges in English teaching process use Kurikulum Merdeka. A case study was used as the research design in this study. Interview guidelines and questionnaires were used as the instruments to get the data. The participants were five English teachers from four Junior high schools in Bogor, Jawa Barat, Indonesia. The result or findings showed that English teachers enacted agency in their teaching process used Kurikulum Merdeka with several characteristics, namely: Teacher Intentional Action, Teacher Autonomy, Teacher Professional Growth, Teacher Collaboration and Teacher Contextualization. And there are several problems or challenges in teaching English used Kurikulum Merdeka, such as: lack of information, lack of facilities and infrastructure, and students' abilities. To solve the problems or to face the challenges collaboration from government, school support, teachers, parents and students is needed.